Geometrical features underlying the perception of collinearity. (November 2016) - Morgan, Michael; Dillenburger, Barbara
Abstract: The magnitude of the Poggendorff bias in perceived collinearity was measured with a 2AFC task and roving pedestal, and was found to be in the region of 6–8 deg, within the range of previous estimates. Further measurements dissected the bias into several components: (1) The small (∼1 deg) repulsion of the orientation of the pointer from the parallel, probably localized in the part of the line near the intersection (2) A small (<1 deg) location bias affecting the intersection of pointers and inducing lines; and (3) A larger (>1 deg) bias in the orientation of virtual lines crossing the gap between two parallels, towards the orientation of the parallels, or equivalently (4) An orthogonal bias in actively constructing a virtual line across the gap. We conclude that orientation repulsion by itself is an inadequate explanation of the Poggendorff effect, and that a full explanation must take account of the way in which observers construct virtual lines in visual space in order to carry out elementary geometrical tasks such as extrapolation.